PEMBANGUNAN PERTANAHAN DI INDONESIA: SERTIFIKAT GANDA HAK ATAS TANAH MENURUT PERATURAN PEMERINTAH NO. 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - Ratna D. E. Sirait; Tiromsi Sitanggang (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
The purpose of this research is to find out the factors that led to the occurrence of multiple certificates of land rights and how BPN's responsibility for the disadvantage of the losing party and as evidence of the cancellation of land rights by PTUN. The results showed that the factors which bring out to the occurrence of multiple certificates of land rights were intentional, unintentional and administrative errors. The emergence of multiple certificates can occur due to the fault of the land owner himself, who does not pay attention to his land and makes good use of it, so that it is controlled and used by others, over time it is registered in his name. land in carrying out their duties. Those who are responsible both morally and materially, if a land dispute occurs due to multiple certificates of land rights caused by negligence and/or other intentional elements of the BPN officers themselves, causing material and immaterial losses, then the one who should be responsible is BPN.